Towards learning organization in education sector: an analysis on emotional intelligence competencies among UNITAR staff / A'dillah Mustafa - Mustafa, A'dillah (2002)
The main purpose of this study was to identify the Emotional Intelligence levels of UNITAR staff. Primary data was collected using questionnaire. One hundred questionnaires were equally distributed to the Lecturer and Administrative staff, and a total of 80 returned their responses. Data collected was analyzed using SPSS Computer Software Program. The result indicated that there is a significant correlation between the position of Lecturer and Emotional Intelligence levels. Lecturers were found to be having more Emotional Intelligence due to their nature of job that requires them t regularly communicate with others. The second finding is that there is no significant correlation between gender and Emotional Intelligence. This shows that gender is not a good predictor of Emotional Intelligence. The third hypotheses on the Emotional Intelligence levels of Universiti Tun Abdul Razak (UNIT AR) were found to be moderately well level. Lastly the result can be concluded as the more we communicate the higher Emotional Intelligence level we may have.